Distribution and driving factors of settlement heritage of coastal peninsulas via GIS: evidence from Shandong, China - Liang, Qibai; Pan, Zhao; Huang, Yuhao; Zheng, Liang; Fang, Jiaying; Qin, Yuanrui; Zhu, Yufei; Kang, Lulong; Chen, Yile (Frontiers in Earth Science, 2025)
Settlement heritage refers to the remains of human settlements with historical, cultural, and scientific value. It represents the social and architectural remains left by humans at a specific time and place. It can also refer to a settlement, the formation and characteristics of which are inherently valuable for research. Settlement heritage is the result of the interaction between human activities and the natural environment in historical periods. Extracting their rich historical and cultural information is of positive significance as it contributes to the development of modern industries. This study, using Shandong Province as an example, examines the distribution pattern and driving factors of settlement heritage in coastal peninsulas. We first screened 580 settlement heritages information points by collecting Chinese settlement heritage lists and verifying them through field surveys. GIS geographic information analysis technology and field survey data collection quantitative research methods were used. The research results show that: 1. The spatial distribution of settlement heritage in Shandong Province shows significant clustering characteristics, and the high-density distribution areas have obvious multicentricity. The central Shandong region, the Jiaodong Peninsula, the southern Shandong region, and the northern Shandong region are the main concentrations of the traditional high-density areas. 2. The number of settlement heritages in Weifang City and Yantai City are 110 and 95, respectively, which accounts for the highest proportion in the province and has a high geographical concentration. They are the core areas of the distribution of settlement heritage in the province. 3. The distribution of the 580 settlements heritage in Shandong Province is generally dominated by the topography of the natural environment. Cultural landscape sites and historical heritage spaces have a greater impact on the distribution of settlements. Cultural and folk areas, along with slopes, significantly influence the distribution of settlements.